Social Learning in Food Quality Governance – Evidences from Geographical Indications Amendments. Issue 1 (18th February 2020) - Edelmann, Hanna; Quiñones-Ruiz, Xiomara Fernanda; Penker, Marianne; Scaramuzzi, Silvia; Broscha, Kristina; Jeanneaux, Philippe; Belletti, Giovanni; Marescotti, Andrea
Food producers can define collective quality standards and legally protect the origin, characteristics, traditions and the reputation of a place-based product through geographical indications (GIs). Producers, processors and other relevant actors in the GI production system codify and adapt their production rules via the GI Product Specification and possible amendments. Based on the Management and Transition Framework (Pahl-Wostl et al. 2010 ), we developed a framework to analyze the role of social learning in food quality governance and adaptation. We analyzed as case studies two cheeses protected by a Protected Designation of Origin, Laguiole (France) and Bitto (Italy). They were selected according to diverse institutional contexts, existing amendments of the Product Specification, and access to documents and interviewees willing and capable to recall the amendment processes. A comparative case study approach served to analyze the amendment processes embedded in different arenas for social learning. Actors amended their Product Specification due to both system-internal (e.g., locally generated knowledge, negotiation processes) and external (e.g., market evolution, new breeds/varieties) pressures. In the two cases, there have been social learning processes among local producers, with diverging outcomes. The results shed light on the dynamic interactions of the drivers for amendments, knowledge generation and integration processes, social learning and negotiation, learning outcomes as well as re–evaluation and re-negotiation. The design of multi-level social learning arenas can help protecting the product identity of evolving social-ecological systems and may contribute to a consistent and long-term strategy going beyond short-term local pressures.